Modeling HIV Pre-Exposure Prophylaxis - Straubinger, Thomas; Kay, Katherine; Bies, Robert (Frontiers in Pharmacology, 2020)
Pre-exposure prophylaxis (PrEP) has emerged as a promising strategy for preventing the transmission of HIV. Although only one formulation is currently approved for PrEP, research into both new compounds and new delivery systems for PrEP regimens offer intriguing challenges from the perspective of pharmacokinetic and pharmacodynamic modeling. This review aims to provide an overview the current modeling landscape for HIV PrEP, and highlight promising or interesting compounds and formulations.